An application of the finite difference method for solving the mass spring system equation - Gabariela Purnama Ningsi; Fransiskus Nendi; Lana Sugiarti (Department of Mathematics, Hasanuddin University, 2020)
The numerical method is one method that can be used to solve differential equations, both differential equations that are easy or difficult to solve analytically. The solution obtained from the calculation results is an approximate solution or a solution that approaches an analytic solution, not an analytic solution. That is, in solving differential equations numerically, there is always an error. In this paper, an analytical solution is described and described and the application of different methods in solving a damped mass spring system with a known limit value. The error between the analytic and numerical solutions obtained is very small.